THE ROLE OF PROBLEM ASSETS IN ENSURING THE FINANCIAL STABILITY OF COMMERCIAL BANKS - Uktamova Nozima Narzulla kizi (Journals Park Publishing, 2023)
This article discusses the situation of commercial banks in Uzbekistan with problem loans, their recovery methods, and problems. Besides, indicators of problematic assets of banks operating in the country have been analyzed.
Keywords: problem assets, commercial banks, credit, creditor, debtor.